Anxious animation (1994-2004) - Klahr, Lewis; Ascher, Rodney; Garon, Syd; Geiser, Janie; Henry, Eric; Trainor, Jim ([United States] : Other Cinema, 2006)
Spokes from the wheel of torment (2004) (2:00) / directed and animated, Syd Garon and Eric Henry ##- Lulu (1996) (3:00) / Lewis Klahr ##- Immer Zu (1997) (9:00) / Janie Geiser ##- Sneak attack from Wave twisters (2000) (4:00) / [Henry Garon Ascher] ##- The bats (1998) (8:00) / by Jim Trainor ##- Altair (1994) (8:00) / Lewis Klahr ##- Rodney & Syd's movie of Jack Chick's Somebody goofed (1998) (9:00) / directed, animated, edited by Rodney and Syd ; story and characters by Jack T. Chick ##- Lost motion (1999) (11:00) / Janie Geiser ##- Pony glass (1997) (15:00) / Lewis Klahr ##- Highlights of the Permian Era series, no. 1. The Moschops (1999) (13:00) / written & animated by Jim Trainor.
Onderzoek KASK Professioneel (OFVP)
film
Keywords: Klahr, Lewis; Geiser, Janie; Trainor, Jim; Henry, Eric; Garon, Syd; Ascher, Rodney